As revoltas de Junho de 2013: uma cartografia afetiva dos enunciados e das imagens do levante brasileiro - Cunha, André Arias Fogliano de Souza (2017)
The thesis is a semiotic and biopolitical approach to the revolts of June 2013 that occurred in Brazil. The Brazilian uprising is apprehended, in connection with the world-struggles taking place since 2011, as an aberrant semiosis. This semiosis has destabilized the present state of things and words with which the governamentality of integrated world capitalism operates locally and worldwide. The research problem pursued through the work is to evaluate the mode in which the processuality of affects, statements and images was expressed in a complex network of sense and sensations, taking into account the macro and micro political vicissitudes resulting from the current neoliberal logic. The hypothesis mobilized consists of affirming this aberrant semiosis as a movement that has abolished the state of perception consensually established into what is now conventionally defined as the Anthropocene, thereby unleashing a relational field of conceptual experimentation. The relevance of such a study resides in the fact that the June rebellions have generated a transvaluation of the actual perceptual and discursive regime, which must be studied in order to reach a adequate understanding of the contemporary semiotic-political context. The aim of this research is to cartograph the logical concatenation of the revolt’s semiosis, tracing the affects, images and enunciates proliferated in its interstices. Hence, it’s necessary to recalibrate or to recreate the concepts available according to the frequencies irradiated during the upheaval. The specific objective is to manage modalities of critical readings connected to an ethico-aesthetical paradigm along with the multinaturalist perspectivism. The conclusion reached points to a possibility to establish, following the current cycle of world-struggles, a diagnostic procedure to the events’ sign surface, named as a savage or perspectivist semiotics. Thereunto, it puts in motion a conceptual machine in alliance with philosophical thought produced by Espinoza, Deleuze, Guattari, Foucault, Viveiros de Castro, Pelbart, Manning, Rolnik, etc